Acidic environments trigger intracellular H+-sensing FAK proteins to re-balance sarcolemmal acid–base transporters and auto-regulate cardiomyocyte pH - Wilson, AD; Richards, MA; Curtis, MK; Gunadasa-Rohling, M; Monterisi, S; Loonat, AA; Miller, JJ; Ball, V; Lewis, A; Tyler, DJ; Moshnikova, A; Andreev, OA; et al. (Oxford University Press, 2021)
Aims In cardiomyocytes, acute disturbances to intracellular pH (pHi) are promptly corrected by a system of finely tuned sarcolemmal acid–base transporters. However, these fluxes become thermodynamically re-balanced in acidic environments, which inadvertently causes their set-point pHi to fall outside the physiological range. It is unclear whether an adaptive mechanism exists to correct this thermodynamic challenge, and return pHi to normal.